Technology-Based Teacher Training and Enhancement of 21st-Century Competencies: A Systematic Review - Manuel, Joshep E (International Education Trend Issues, 2025)
The technological advancements of the 21st century have transformed educational paradigms, requiring teachers to shift from mere transmitters of knowledge to facilitators of dynamic, collaborative, and technology-driven learning environments. This article examines the role of technology-based teacher training in fostering the development of 21st-century competencies, including critical thinking, creativity, communication, collaboration (4Cs), and digital literacy. Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, the study reviewed 27 empirical articles published between 2019 and 2025, sourced from Scopus, Google Scholar, ERIC, and DOAJ. The findings reveal that technology-based training enhances teachers’ digital literacy through the Technological Pedagogical Content Knowledge (TPACK) framework, promotes innovative pedagogical transformations such as flipped classrooms and project-based learning, and strengthens professional collaboration through Professional Learning Networks (PLNs). These outcomes underscore that practical training must go beyond technical proficiency to include pedagogical transformation and the cultivation of an innovative mindset. The article concludes that technology-based teacher training significantly enhances teachers’ capacity for 21st-century education and recommends contextually designed, sustainable training that is supported by educational policies and adequate digital infrastructure.